The Purple Sweet Potato Body Scrub Cream Formulation - Wirasuta, I Made Agus Gelgel; Triastuti, Ni Komang Dewi; Deviyanthi, Kadek Sintia; Sartika, Dyah Aryani; Utari, Putu Dyah (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Anthocyanin is active compound of purple sweet potato, has effect as anti-oxidative, anti-inflammatory, and anti-itching, make them interesting ingredients for skin treatment. The body scrub is one of popular cosmetic product in SPA industry. Their stability property is one crucial factor to develop a purple sweet potato body scrub cream. The steam and oven heating of tuber were involved on the scrub powder preparation.The oven and non-heating preparation scrub powder provided fine-sized powder more than 50%, but the steaming produced granular particle distribution. Total anthocyanin content in scrub grains was 326.8 mg/100 g for steam preparation, 103.3 mg/ 100 g for oven, and 34.4 mg/100g for non-heating, respectively. The steamed scrub powder preparation method produced stabile anthocyanin content in body scrub cream for 25 days observation.Â Â